2015
DOI: 10.1088/0960-1317/25/7/074001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sputter deposition parameters on molybdenum nitride thin film properties

Abstract: Molybdenum and molybdenum nitride thin films are presented, which are deposited by reactive dc magnetron sputtering. The influence of deposition parameters, especially the amount of nitrogen during film synthesization, to mechanical and electrical properties is investigated. The crystallographic phase and lattice constants are determined by x-ray diffraction analyses. Further information on the microstructure as well as on the biaxial film stress are gained from techniques such as transmission electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…In a very recent paper, Stöber et al [32] have reported results quite consistent with the previous work. The molybdenum nitride films about 150 nm thick are deposited by reactive dc magnetron sputtering at power ranging from 300 to 700 W and a total pressure ranging from 2 to 8 × 10…”
Section: Reactive Sputtering Methodssupporting
confidence: 79%
See 3 more Smart Citations
“…In a very recent paper, Stöber et al [32] have reported results quite consistent with the previous work. The molybdenum nitride films about 150 nm thick are deposited by reactive dc magnetron sputtering at power ranging from 300 to 700 W and a total pressure ranging from 2 to 8 × 10…”
Section: Reactive Sputtering Methodssupporting
confidence: 79%
“…Stöber et al [32] have also reported an increase of the resistivity of Mo2N films with increasing nitrogen fraction in (Ar-N2) gas mixtures. The resistivity of Mo2N films deposited at 20% of nitrogen fraction, a pressure of 500 W and a total pressure of 8 × 10…”
Section: Molybdenum Nitride Films Prepared By Reactive Sputteringmentioning
confidence: 88%
See 2 more Smart Citations
“…On the other hand, Stöber et al reported that at 50% nitrogen content the Mo-N thin form crystallite sizes of 6.4 nm and a more pronounced texture of the γ-Mo 2 N structure [34]. Saito and Asada have reported a phase change from the cubic γ-Mo 2 N to a B1-type MoN by increasing the N 2 + ions implanted in sputtered Mo thin films at room temperature [35].…”
Section: Structural Propertiesmentioning
confidence: 99%